ANALISIS POLA KOMUNIKASI ANTAR PRIBADI PSIKIATER DENGAN PASIEN GANGGUAN JIWA (DEPRESI) MELALUI METODE TERAPEUTIK DI KLINIK UTAMA SUDIRMAN MEDICAL CENTRE DENPASAR - Widhiawati, Gst Ayu Putu; Suryawati, I.G.A Alit; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT This study aims to determine and identify how forms of interpersonal communication that occur in psychiatrists and mental patients (depression) as well as to know and identify how the communication process barriers that occur in psychiatrists and mental disorders patients (depression). The results show that the SMC clinic uses the principles of therapeutic communication that also has similarities with the basic principles of interpersonal communication, including: therapeutic communication is a transaction process, the relationship in therapeutic communication is seen as a complementary relationship, therapeutic communication has dimensions of content and relationships , therapeutic communication is an adjustment process, therapeutic communication is a series of punctuation events, therapeutic communication is inevitable, irreversible and cannot be repeated. Keyword : Interpersonal communication, terapeutic communication, therapeutic methode.